Evaluasi Program Trans Serasi dalam Pelayanan Angkutan Siswa Gratis di Kabupaten Tabanan (Studi Kasus di Kecamatan Tabanan, Kabupaten Tabanan) - Arvianti, Ade Evita; Purnamaningsih, Putu Eka; Supriliyani, Ni Wayan (CITIZEN CHARTER, 2020)
ABSTRACT The Trans Serasii Program is an innovative program aimed at facilitating student free transportation to junior highmschoolgstudentskinpTabananoRegency. The beginning implementation of this program targeted SMPmN 1, SMPmN 2, and SMPmN 3 Tabanan. This researchmusesmdescriptive qualitative method with data collection techniques such as observation, interviews, andodocumentation. The results of the study are based on an analysis with six indicators of policy evaluation according to William N. Dunn which showing that the program has not been implemented or running well because there are still problems with several indicators such as effectiveness in ensuring student safety and comfort due to lack of fleets, efficiency of human resources due there are still drivers who violate the rules, there are no local regulation yet that specifically regulate this program, and the equipment is not optimal. Keywords: Evaluation, Trans Serasi Program, Tabanan District, Tabanan Regency